Analisis Antrian Kapal di Dermaga 5 Pelabuhan Banten - Nugraheni Djamal; Haris Eno Maulana (Universitas Serang Raya, 2018)
Pelabuhan Banten is a company engaged in port services in Indonesia, one of the essential aspects of which is the process of loading and unloading ships which are part of the landing process that will affect the queue of vessels entering or exiting the port. In this case, the variables observed were data on the time of arrival, service time, and the number of services. The method used in the retrieval of data on arrival time is purposive sampling. Data analysis methods include the detection of data distribution, determination of the queue model, and performs the calculation of the queue model. The single phase multichannel queuing system used in Banten Port for the average arrival of ships (λ) is obtained 45 ships/month and the average service (µ) adds 2 servers, from 3 servers to 5 servers because of the calculation of the 5 servers obtained the results of the calculation of the queue model are obtained. The probability of no service (Po) is 0.023. The average number of waiting in the queue (LQ) is 26 ships. The average number of waits in the system (Ls) is 35 ships. Average waiting time in the queue (Wq) is 34.66 minutes, the average waiting time in the system (Ws) is 35.99 minutes..